FOREIGN EXPERIENCE OF SOCIO-ECONOMIC REINTEGRATION OF DEMOBILIZED WAR VETERAN AND ITS POSSIBLE IMPLEMENTATION IN UKRAINE - Poita, Iryna; Kalinichenko, Olena (Zhytomyr Ivan Franko State University, 2019)
Article peresvyachena analysis leading foreign experience and develop training and educational measures aimed at shaping the economic behavior of demobilized participants and ATO veterans, acquiring them new financial and entrepreneurial competences; study, development, testing and implementation of training programs and workshops. The article is aimed at increasing the degree of socio-economic adaptation, the level of economic literacy and the development of entrepreneurial initiatives to open its own business to demobilized participants and veterans of the Zhytomyr anti-terrorist operation, who left the Armed Forces of Ukraine and return to civilian life. Measures of socio-economic adaptation of military personnel involved in long-term military conflicts and sources for financing of relevant measures by both the state and business are proposed. Business can count on information-consulting support, but it can to be effective in the case of coordinated and concerted action at both national and regional levels, attracting such support from business representatives under public-private partnerships.